La Posmodernidad. Nuevo régimen de verdad, violencia metafísica y fin de los metarrelatos - Vásquez Rocca, Adolfo (Nómadas. Critical Journal of Social and Juridical Science, 2011)
Here is a brief notes about the notion of postmodernity. An introductory text that attempts to shed light on some topics that are intertwined and problematize a little over 30 years since the publication of La Condition posmoderna of Jean-François Lyotard. This condition is, according to Lyotard's own say-condition of knowledge in more developed societies, particularly in the Americas, in pen and critical sociologists. The postmodern is not "opposite" of the modern, but its excess. It is modernity itself that in its self reversed their modalities and cultural effects. The discrediting of reason, science and technology has emerged from a "mere denial" of these, but its factual and historical specificity of their realization. Postmodernism means the state of culture after the changes that have affected the rules of the game of science, literature and art from the nineteenth century. Here we place these transformations in relation to the crisis of the great stories. It is "postmodern" incredulity about metanarratives. This is undoubtedly an effect of scientific progress but that progress in turn presupposes it. With disuse metanarrative legitimation device responds particularly the crisis of metaphysical philosophy, and of the university depended on it.
Keywords: Postmodern narrative reason; Fragment; Narrative; Time; Completeness; Design; Aesthetic; Dialectical; Speech; Simulation; Ethics